APPLICATION OF MAGNETIC AND INDUCED POLARIZATION METHOD FOR DELINEATING GOLD-BEARING VEIN ZONES AT CIBALIUNG, PANDEGLANG REGENCY, BANTEN - Muhammad Sidiq; Y. Yatini; Agus Fajrin (Puslitbang tekMIRA, 2021)
Magmatic processes occurred during the Miocene period caused the formation of epithermal gold deposits in Cibaliung area. The deposit has previously been investigated through geological surveys which basically only covers the surface aspect, so in this study a subsurface analysis was carried out through magnetic and IP surveys to determine the distribution and continuity of the gold deposits. The magnetic survey was conducted over an area of about 3 km2 with sampling interval 20 m east and 100 m north. The magnetic data were processed using Oasis Montaj with magnetic intensity map as an output, which was then interpreted to determine the presence of structures and magnetite destruction zones as mineralization clues. The IP survey was conducted on 20 east-west oriented lines with length of about 1.2 km. The electrode configuration used is Wenner with 25 m spacing. IP data were processed using RES2DINV software to eliminate bad datum points and invert the apparent chargeability values into the true ones. IP data are then interpreted to clearly determine the position, direction, and distribution of gold mineralization body by detecting the presence of sulfide minerals as ligands carrying gold. Magnetic data analysis shows that gold mineralization tends to occur at low magnetic anomaly, ranging from 37 nT to 240 nT and generally associated with northwest-oriented structures. The mineralization zone is found in four main vein zones with resistivity and chargeability values < 51 and > 50 ms.